Implementasi Nilai –Nilai ( Sipakatau, Sipakalebbi, Sipakainge ) dalam Pengembangan Karakter Peserta Didik Di SMKN 4 Bone - Tasya Annisaul Khaerani; Arisal A; Singkeru Rukka (JURNAL MAPPESONA, 2025)
Cultural values, particularly the values of sipakatau, sipakalebbi, and sipakainge, are crucial to be applied in the development of students' character within the educational environment. Schools serve as a second home after the family home, where children gain knowledge and develop their personalities. Therefore, it is essential for all school members to implement and integrate these cultural values into their daily lives. Although these values have been instilled, there are still many students who deviate from them, indicating the need for optimization in their application. This study aims to analyze the implementation of the values of sipakatau, sipakalebbi, and sipakainge in character education at SMKN 4 Bone, focusing on the challenges faced by educators, particularly in online learning. The findings show that despite efforts to instill these cultural values, some students still violate rules, such as skipping school and not adhering to the dress code. Therefore, further efforts are needed to raise awareness about the importance of cultural values in shaping students' character in school.